Analisis pengaruh diameter pipa terhadap perubahan sub-regime pola aliran 2 fasa stratified air-udara pada pipa horizontal - Rahmandhika, A.; Hendaryati, H.; Mokhtar, A. (Dinamika Teknik Mesin, 2024)
Stratified water-air flow is very common and expected to occur in piping systems. Understanding the characteristics of liquid hold-up in stratified flow patterns is considered one of the important factors in operational financing for gas and liquid transportation in various industries. This study aims to determine the pipe diameter effect on the parameters of stratified flow pattern sub-regime. The data obtained in this study is used as a supporting database as a basis for developing the piping system design. The research was conducted on acrylic pipes with diameters of 16 and 26 mm and a length of 9.5 m. The method applied to determine the characteristics of the stratified flow pattern is the constant current (CECM). The observation area is located 220 – 260 D from the inlet. The value range of JL = 0.03 – 0.1 m/s and JG = 2.83 – 10 m/s. Based on the experiment, the results obtained from the liquid hold-up affect the criteria for sub-regime changes in stratified flow patterns. The liquid hold-up is affected by the superficial velocity of the liquid, gas, and inner pipe diameter. The higher the liquid's superficial velocity, the greater the liquid hold-up value. The higher the gas superficial velocity, the smaller the liquid hold-up value. At low JL, an increase in JG causes a sub-regime transition of the flow pattern from smooth stratified to wavy stratified. At high JL, an increase in JG causes a transition of the flow pattern sub-regime from pseudo slug to roll wave and wavy stratified.